MEASURING THE JOB PRECARIOUSNESS EXPERIENCED BY GOJEK DRIVERS IN INDONESIA - Mohammad Farid Budiono (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
The introduction provides an overview of the rapid growth of digital technology and its impact on various aspects of human life. The rise of the information society and the development of the digital economy, particularly in Indonesia, has led to the emergence of start-ups like Gojek. Gojek, a digital business offering various services, has become a significant player in the Indonesian market, impacting millions of lives and employing many driver-partners. However, the welfare of Gojek drivers has come under scrutiny as studies have highlighted their vulnerabilities. The concept of "precariat," introduced by Guy Standing, is used to describe the vulnerabilities experienced by these digital workers. Precariat workers, such as Gojek drivers, face multiple challenges, including ambiguous work relations, lack of worker rights, and inadequate state support. The methods section explains the research approach used, which is a qualitative descriptive method with a literature review approach. The research framework is based on data collected from various sources to analyze Gojek drivers' vulnerabilities. The results section provides insights into Gojek's profile, industry development in Indonesia, and the vulnerabilities Gojek drivers face. The partnership status of Gojek drivers leads to unequal relationships, extended working hours, and a lack of worker rights, particularly regarding social security benefits. Additionally, conflicts have emerged between Gojek and conventional motorcycle taxis, further highlighting the job insecurity experienced by Gojek drivers.